Introduction to modern EW systems - De Martino, Andrea (Boston; London: Artech House, 2018)
The second edition has been greatly expanded to include a wealth of new material, from remote piloted airborne systems, directed energy weapons, and noncooperative air surveillance, to electronic warfare (EW) radar band sensor next generation architectures, real-time data links, and smart jamming.
Introduction to electronic warfare scenarios -- Evolution of signal emitters and sensors -- EW RF band sensor systems -- RF direction finding and emitter location techniques -- Electronic countermeasure systems -- ECM techniques and sensor ECCMs -- Signal detection in sensor receivers -- Introductory concepts of estimation theory -- Antennas and phased array antennas -- Analog modulation methods -- Evaluation of BER increase for noise and CW tone jamming in communication systems employing BFSK modulation -- Radar pulse compression waveforms.
Includes bibliographical references and index.
Keywords: Electronics in military engineering; Electronic countermeasures